Doping Calcia and Yttria into Zirconia Obtained from by Product of Tin Concentrator to Improve its Ionic Conductivity - Fitria Rahmawati; Bambang Prijamboedi; Syoni Soepriyanto; Ismunandar Ismu (Institute for Research and Community Services (LPPM) ITB, 2011)
Zirconia has been prepared from Zircon concentrate by caustic fusion methods. Zircon is a by product from tin ore concentration plant at Bangka island of Indonesia. Yttria Stabilized-Zirconia (YSZ) was prepared by introducing the 8 % mol yttrium oxide into zirconia and sintered at 1500